The Effect of Audit Fees, Audit Opinions, and Audit Delays on Switching Auditors: Case Study on Companies in The Goods and Consumer Industry Sector Listed on The Indonesia Stock Exchange for the 2015-2020 Period - Debora, Grace Artha; Subiyanto, Bambang; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to empirically examine the effect of Audit Fees, Audit Opinions, and Audit Delay on Switching Auditors in Goods and Consumer Industry Sector Companies Listed on the Indonesia Stock Exchange for the 2015-2020 Period. The data in this study was obtained from secondary data on the annual financial statements of companies in the goods and consumption industry sector for the period 2015-2020. In sampling in this study, purposive sampling was used. The analysis technique in this study is binary logistic regression analysis processed using SPSS 26. Based on the results of partial research, it was found that Audit Fee has a negative and significant effect on Switching Auditors, Audit Opinion has a negative and significant effect on Switching Auditors, Audit Delay does not affect Switching Auditors